Synthesis and biological evaluation of hoshionolactam-based compounds - Jachak, Gorakhnath R.; Elizebath, Drishya; Shukla, Anurag; Shanmugam, Dhanasekaran; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2021)
In search of novel antitrypanosomal agents based on hoshinolactam (IC50=3.9 nM), we disclose the synthesis and biological evaluations of 14 different analogues of the natural product using combinations of different acids and lactams. Antitrypanosomal activity assays revealed that the synthesized analogues were less potent than the parent natural product.
Keywords: Hoshinolactam; Ozonolysis; Parasitic diseases; Trypanosoma